2006
DOI: 10.1111/j.1523-1739.2005.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Habituation of Adult Magellanic Penguins to Human Visitation as Expressed through Behavior and Corticosterone Secretion

Abstract: Ecotourism is increasing worldwide; hence, it is important to know how wildlife are affected behaviorally and physiologically by human visitation. We studied the effects of human visitation on the Magellanic Penguins (Spheniscus magellanicus) at Punta Tombo, Argentina, by monitoring changes in defensive head turns and plasma corticosterone (a hormone secreted in response to stress) for penguins with and without a history of tourist visitation. Habituation to human visitation was rapid. In penguins with no prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
164
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(179 citation statements)
references
References 44 publications
11
164
0
4
Order By: Relevance
“…As penguins are commonly used as model species for hormonal and stress studies in birds (e.g. Holberton et al, 1996;McQueen et al, 1998;Fowler, 1999;Walker et al, 2005b;Walker et al, 2006), our results will be particularly valuable for the interpretation of previous studies, and for the undertaking of future studies.…”
Section: Introductionmentioning
confidence: 99%
“…As penguins are commonly used as model species for hormonal and stress studies in birds (e.g. Holberton et al, 1996;McQueen et al, 1998;Fowler, 1999;Walker et al, 2005b;Walker et al, 2006), our results will be particularly valuable for the interpretation of previous studies, and for the undertaking of future studies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in field studies of species ranging from primates (Williamson & Feistner 2003;Aguiar & Moro-Rios 2009) Walker et al 2006), and has played a crucial role in elucidating the socio-ecology of many of these species.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that having to cross a tourist footpath to reach their nest when entering or leaving the colony did not have increased basal CORT. In adults, penguins that lived near tourist areas had a diminished CORT response to capture stress than those living in more isolated areas (Fowler, 1999; Walker et al., 2006). Additionally, individuals living in more isolated areas had higher basal CORT than those living in tourist areas (Fowler, 1999).…”
Section: Discussionmentioning
confidence: 99%